Design of Postgraduate Thesis Exam Registration and Scheduling Information System For IAIN Palangka Raya - Sapto Pamungkas; Suparno Suparno; Abdul Qodir; Pujiati Astuti; Mualimin Mualimin (Forum Kerjasama Pendidikan Tinggi, 2023)
The design of an information system for registration and scheduling of postgraduate thesis exams at IAIN Palangka Raya is a system that will be built to make it easier for users to operate the system in managing thesis exams. This information system provides facilities to users who can interact in accordance with standard operating procedures according to user needs. As for the users involved in it, such as: students, academics, study programs and directors. This information system will contain activities starting from submitting a thesis title, determining a supervisor, making a supervisor's decision, thesis guidance, registration and scheduling of thesis proposal seminars as well as thesis examination seminars along with attached documents for each activity. The research method used is a structured method (waterfall model). This information system is designed and built usingCSS, Html, PHP, Auto Generate, Boostrrap and Mysql. The result of this research is the achievement of creating a web system that is expected to facilitate the management of registration and scheduling of quality thesis examinations at the Postgraduate IAIN Palangka Raya. Researchers also suggest that this research can be developed according to user needs